The precipice - Doiron, Paul (New York : Minotaur Books, 2015)
"When two young female hikers disappear in the Hundred Mile Wilderness--the most remote stretch along the entire two-thousand mile Appalachian Trail--Maine game warden Mike Bowditch joins the search to find them. The police interview everyone they can find who came in contact with the college students and learn that the women were lovers who had been keeping their relationship secret from their Evangelical parents in Georgia. When two corpses are discovered--the bones picked clean by coyotes--rumors spread that the women were stalked and killed by the increasingly aggressive canines. Faced with a statewide panic, Maine's governor places an emergency bounty on every dead coyote, and wildlife officials are tasked with collecting the carcasses. Despite some misgivings, Bowditch does his grisly job. But he finds his complacency challenged by his new girlfriend, the brilliant but volatile biologist Stacey Stevens, who insists coyotes merely scavenged the bodies after the women were murdered. When Stacey herself disappears on the outskirts of the Hundred Mile Wilderness, Bowditch realizes that locating her means he must also discover the truth behind what happened to the two hikers. Were the young women really killed by coyotes or, as Stacey insisted, were they murdered by the most dangerous animal in the North Woods?"--
Keywords: Game wardens -- Fiction; Young women -- Crimes against -- Fiction; Murder -- Investigation -- Fiction; Missing persons -- Investigation -- Fiction; Wilderness areas -- Maine -- Fiction; FICTION / Mystery & Detective / General; Mystery fiction; Suspense fiction